Cu‐Isotope Evidence for Subduction Modification of Lithospheric Mantle. (25th August 2022) - Kempton, Pamela D.; Mathur, Ryan; Harmon, Russell S.; Bell, Aaron; Hoefs, Jochen; Shaulis, Barry
Abstract: Ultramafic xenoliths from southeastern Arizona, USA, provide evidence for Cu‐isotope heterogeneity in the lithospheric mantle. We report new data on Type I (Cr‐, Mg‐rich) peridotites, but also the first Cu‐isotope data for Fe‐Ti‐Al‐rich Type II pyroxenite (±amphibole) xenoliths. Whole rock δ 65 Cu values of the pyroxenites and cryptically metasomatized Type I lherzolites range to isotopically heavier compositions than asthenospheric mantle (i.e., up to +1.44‰ and +1.12‰, respectively, vs. ∼ 0‰ ± 0.2‰). Copper leached from the xenoliths using aqua regia, assumed to be hosted in interstitial sulfides, is even more variable (δ 65 Cu −0.78 to +3.88‰), indicating considerable isotopic heterogeneity within individual samples. Host basalts have low δ 65 Cu (−0.23‰ to −1.30‰), so basalt—xenolith interactions are not responsible for the compositional variations observed. While mass‐dependent fractionation may be partly responsible, metasomatism by fluids derived from recycled crustal materials is the predominant control on isotopic variations observed. Amphibole megacrysts and amphiboles separated from Type II amphibole‐bearing clinopyroxenite have normal, mantle‐like 18 O/ 16 O ratios but H‐isotope compositions (δ 2 HSMOW −82‰ to −45‰) that range between that of nominally anhydrous mantle (−80 ± 10‰) and seawater (0‰). Host basalts are also enriched in 34 S relative to depleted asthenospheric mantle, having δ 34 SCDT values up to +8‰, i.e., compositions commonly attributed to a component of recycled seawater or hydrated oceanic crust. These new data suggest that formation of Type II metasomes in the lithospheric mantle beneath the Basin and Range Province was associated with subduction of the Farallon plate and not alkali basalt magmatism associated with Basin and Range extension. Plain Language Summary: The Cu‐isotope composition of Earth's mantle is believed to be homogenous, with δ 65 Cu varying between −0.2‰ and +0.2‰ (where δ 65 Cu is the 65 Cu/ 63 Cu ratio relative to the NIST976 copper standard). However, samples of the lithospheric mantle entrained as inclusions in Plio‐Pleistocene age basalts from SE Arizona, USA, record a much wider compositional range of −0.78‰ to +3.88‰. The greatest compositional range (−0.08‰ to +1.44‰) is observed in Fe‐, Ti‐, and Al‐rich pyroxenites (±amphibole) that formed by fractional crystallization of basaltic melts in the mantle. While mass‐dependent fractionation in the mantle may be responsible for some of the isotopic variation, metasomatism during subduction, by fluids derived from recycled crustal materials, is proposed as the dominant mechanism. These new data also suggest that formation of enriched veins in the lithospheric mantle beneath the Basin and Range is associated with subduction of the Farallon plate, and not the alkali basalt magmatism caused by Basin and Range extension, as had previously been proposed. Key Points: The Cu‐isotope composition of lithospheric mantle is heterogeneous Metasomatism of this mantle by fluids/melts derived from crustal materials recycled via seduction is the principal source of the heterogeneity Fe‐Al‐rich pyroxenites, representative of geochemically enriched mantle metasomes, exhibit greater isotopic variation than metasomatized peridotites